The Human Milk Oligosaccharide 2′-Fucosyllactose Alleviates Liver Steatosis, ER Stress and Insulin Resistance by Reducing Hepatic Diacylglycerols and Improved Gut Permeability in Obese Ldlr-/-.Leiden Mice - Gart, Eveline; Salic, Kanita; Morrison, Martine C.; Giera, Martin; Attema, Joline; de Ruiter, Christa; Caspers, Martien; Schuren, Frank; Bobeldijk-Pastorova, Ivana; Heer, Marianne; Qin, Yan; Kleemann, Robert (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a complex multifactorial disorder that is associated with gut dysbiosis, enhanced gut permeability, adiposity and insulin resistance. Prebiotics such as human milk oligosaccharide 2’-fucosyllactose are thought to primarily improve gut health and it is uncertain whether they would affect more distant organs. This study investigates whether 2’-fucosyllactose can alleviate NAFLD development in manifest obesity. Obese hyperinsulinemic Ldlr-/-.Leiden mice, after an 8 week run-in on a high-fat diet (HFD), were treated with 2’-fucosyllactose by oral gavage until week 28 and compared to HFD-vehicle controls. 2’-fucosyllactose did not affect food intake, body weight, total fat mass or plasma lipids. 2’-fucosyllactose altered the fecal microbiota composition which was paralleled by a suppression of HFD-induced gut permeability at t=12 weeks. 2’-fucosyllactose significantly attenuated the development of NAFLD by reducing microvesicular steatosis. These hepatoprotective effects were supported by functional transcriptome analyses showing that 2’-fucosyllactose activated ACOX1 (involved in lipid catabolism), while deactivating SREBF1 (involved in lipogenesis). Furthermore, 2’-fucosyllactose suppressed ATF4, ATF6, ERN1, and NUPR1 all of which participate in endoplasmic reticulum stress. 2’-fucosyllactose reduced fasting insulin concentrations and HOMA-IR, which was corroborated by decreased intrahepatic diacylglycerols. In conclusion, long-term supplementation with 2’-fucosyllactose can counteract the detrimental effects of HFD on gut dysbiosis and gut permeability and attenuates the development of liver steatosis. The observed reduction in intrahepatic diacylglycerols provides a mechanistic rationale for the improvement of hyperinsulinemia and supports the use of 2’-fucosyllactose to correct dysmetabolism and insulin resistance.